Pemerolehan Bahasa dalam Film The King’s Speech: Perspektif Behaviorisme dan Sosiokultural - Mustika, Septy; Nucifera, Prima (STKIP PGRI Ponorogo Press, 2026)
This study discusses the process of language acquisition and speech disorders experienced by the main character in the film The King's Speech through the behaviorism and nativism approaches in the realm of psycholinguistics. This film tells the true story of King George VI who had a stutter since childhood, but had to deliver a state speech amidst the pressure of World War II. This study aims to analyze the speech disorders of the main character, as well as how therapeutic interventions and innate language potential can be explained through two main psycholinguistic approaches. The method used is qualitative-descriptive analysis with a literature study approach and content analysis. The results of the analysis show that the behaviorism approach is very relevant in describing the therapy process through reinforcement, repetition, and habits. Meanwhile, the nativism approach is seen through the character's grammatical abilities which remain intact despite obstacles in pronunciation. This study shows the importance of a multidisciplinary understanding of speech disorders, not only from a medical aspect, but also from a linguistic and psychological aspect.